Influence of honing angle on tribological behaviour of cylinder liner–piston ring pair: Experimental investigation. (March 2022) - Baby, Ajith Kurian; Rajendrakumar, P.K.; Lawrence K, Deepak
Abstract: Research conducted on the influence of honing angle on the cylinder liner surface lacks consensus on the numerical value of the honing angle for the desired performance of the liner-ring tribosystem. The paper presents the results of experimental work performed on the cylinder liner samples honed at different angles (20° −100°) to explore the influence of honing angles under boundary lubrication conditions. Experiments conducted at two distinct sliding conditions (0.2 m/s and 0.3 m/s) using a linear reciprocating tribometer indicated 40° as the optimum honing angle based on the evaluation of tribological characteristics such as the coefficient of friction and the wear. Graphical abstract: ga1 Highlights: Study on the cylinder liner samples with different honing angles (20° −100°) under boundary lubrication conditions. Total of 28 experiments were conducted for 0.2 m/s and 0.3 m/s sliding velocities. The lowest COF value was obtained for a honing angle of 40°, while 80° showed the highest value. 40° specimens showed lowest minimum deviation of Sz value at 0.2 m/s and at 0.3 m/s it was shown by 100°. Experimental results indicated 40° as the optimum honing angle based on the evaluation of friction and the wear attributes.